Improvement in the prediction of gasoline pool fire behaviour: CFD modelling and validation. (November 2020) - Uribe, Sebastián; Zárate, Luis; Suo-Anttila, Ahti; Cordero, Mario E.; Smith, Joseph D.
Abstract: The development and implementation of mathematical models through Computational Fluid Dynamics (CFD) techniques has been acknowledged as a promising tool for the prediction of hydrocarbon pool fires behaviours. In this sense, different approaches, with different assumptions and simplifications, and accounting for different phenomena, have been developed in the literature. However, the deviations in the predictions of the experimentally determined parameters, such as temperatures profiles, flame heights and radiative heat flux, by the implemented models are still high. Therefore, the implementation of these models to predict combustion phenomena and flame behaviours for various scenarios is limited. In this work, the software C3D is used to model gasoline pool fires of different diameters, and under different wind conditions, in order to improve the quality of the predictions of the flame behaviour. The modelled cases correspond to the experimental studies reported in literature. The results from the implemented model show an improved predictive quality when compared with other modelling works reported on literature for the same experimental cases. The deviations in the time averaged temperature, flame height, surface emissive power and radiative heat flux, has been calculated to be 5.0%, 0.05%, 6.32% and 3.82%, respectively. Highlights: C3d is used to model gasoline pool fires of different diameters, under different wind conditions. The model considers a LES model for turbulence, and includes eddy diffusivity on the mass and heat transport equations. The model includes a robust 8-step reaction mechanism to account for gasoline combustions. Improvement in prediction of temperatures, flame height, SEP and radiative heat flux, compared to models found in literature. Deviations of predicted temperatures, burning rate, flame height, SEP and radiative heat flux of 5.0%, 0.5, 0.05%, 6.32% and 3.82%, respectively.